ChemInform Abstract: Fe3O4 Nano‐Particles Supported on Cellulose as an Efficient Catalyst for the Synthesis of Pyrimido[4, 5‐b]quinolines in Water. Issue 1 (17th December 2015) - Edjlali, Laden; Khanamiri, Rahim Hosseinzdeh; Abolhasani, Jafar
Abstract: The employed catalyst can be easily recovered and reused for 5 cycles without significant decrease in activity.